Imaging GPCR internalization using near-infrared Nebraska red-based reagents. Issue 13 (13th March 2020) - Lesiak, Lauren; Zhou, Xinqi; Fang, Yuan; Zhao, Jia; Beck, Jon R.; Stains, Cliff I.
Abstract : Near-infrared reagents for selective labeling of membrane proteins, no-wash imaging, and imaging GPCR internalization. Abstract : Internalization of G protein-coupled receptor (GPCRs) represents a nearly universal pathway for receptor downregulation. Imaging this process provides a means for the identification of pharmaceutical agents as well as potential ligands for orphan receptors. However, there is a need for the further development of near-infrared (NIR) probes capable of monitoring internalization in order to enable multiplexing with existing green fluorescent GPCR activity assays. Our laboratory has recently described a series of near-infrared (NIR) fluorophores in which a phosphinate functionality is inserted at the bridging position of the xanthene scaffold. These fluorophores, termed Nebraska Red (NR) dyes, provide attractive reagents for imaging protein localization. Herein, we disclose the development of NR-based HaloTag ligands for imaging membrane proteins on living cells. These new probes are utilized to image membrane pools of the human orexin type 2 receptor, an established target for the treatment of insomnia. We demonstrate the ability of fetal bovine serum (FBS) to noncovalently associate with a spirolactonized NR probe, enabling no-wash imaging with a 45-fold enhancement of fluorescence. Furthermore, we characterize the utility of NR-based HaloTag ligands for real-time monitoring of receptor internalization upon agonist stimulation. These new reagents enable potential multiplexing with existing GPCR activity assays in order to identify new modulators of GPCR activity as well as ligands for orphan receptors.